Theoretical and Empirical Contributions to the Study of Entrepreneurs - Marulanda Valencia, Flor Á.; Montoya Restrepo, Iván A.; Vélez Restrepo, Juan M. (Cuadernos de Administración, 2014)
Entrepreneurship, especially understood as creation of new enterprises, is a topic of growing interest because, among other causes, of unemployment that stopped being a problem of third-world countries to become a global concern. In its contribution to understanding the phenomenon of “undertaking” and in the figure of the entrepreneurs as its leading players, academics present a series of theoretical proposals to explain their individual characteristics. This work presents an exploration of the main approaches that seek to describe entrepreneurs, starting from a classification proposed based on the literature review on the topic.